Evaluation of the organic and functional results of tympanoplasties through a retro-auricular approach at a medical residency unit - Lima,José Carlos Bolini de (2011)
Tympanoplasty aims at rebuilding the tympanic membrane with or without middle ear functional recovery. AIM: To evaluate the surgical results of tympanoplasties with a retro-auricular surgical approach at a medical residency unit. MATERIALS AND METHODS: Thirty-nine patients with diagnosis of simple chronic otitis media were evaluated; these patients underwent tymplanoplasty by a retro-auricular approach (underlay technique) at a medical residency unit. Patients were included in a prospective medical and audiologic investigation protocol that consisted of a clinical, otomicroscopic and audiometric evaluation. All procedures were supervised by training specialists otorrinolaringology. RESULTS: The rate of surgical success - full integration of the graft - was 95% of cases. Improvement of hearing, as demonstrated in audiometry, occurred in 72% of cases. Improvement in tinnitus was demonstrated subjectively on a visual analog scale in 69% of cases. CONCLUSION: Tympanoplasty through a retro-auricular approach is easy to perform. Full graft integration occurred in 95% of cases and was independent of factors deemed by many authors as relevant. The results - improvement of the quality of hearing and tinnitus - were significant.